IMPLEMENTATION OF THE STATE SUBPROGRAM FOR THE DEVELOPMENT OF AGRICULTURAL EXPORTS - Sergeevich Baleevskikh, Alexander (Revista Inclusiones, 2020)
In the current conditions of the unpredictability of world commodity markets, trade, sanctions, and counter-sanctions wars, the role of non-commodity exports is growing improving the trade balance and developing the economy of the Russian Federation. In this regard, the study raises the timely question of improving Russia's balance of payments through food exports. The importance of this issue is reflected in the instructions of the President and the Government of the Russian Federation, as well as in the State Program for the Development of the Agro-Industrial Complex in the form of a priority national project starting from 2017. The importance and relevance of the study are confirmed by the "New May Decrees" of the President of the Russian Federation, which set a direct task of bringing the volume of exports of food and agricultural products to the level of 45 billion US dollars.